Estudo de caso: o uso da tecnologia BIM e seu nível de maturidade em três escritórios de arquitetura e engenharia da cidade de Macapá-AP - (:unkn) unknown (UNIFAP – Universidade Federal do Amapá, 2024)
Bulding Infomation Modeling - BIM technology is a reality in the world of civil construction, and its applicability and use throughout the entire construction process is evident. The construction market needs to look for ways to reduce costs and deadlines. The insertion of new technologies in the area of Architecture, Engineering and Construction – AEC increasingly contributes to optimizations in the production process. Therefore, tools that make each operation more efficient must be developed with greater qualitative criteria in terms of control, coordination and interaction between the design and execution phases. The objective of this research was to show the level of maturity of three Architecture and Engineering offices in the city of Macapá-AP in relation to the use of BIM as a technological innovation tool. In this way, BIM maturity is a parameter used to evaluate the degree to which this technological tool is inserted in organizations. This objective was achieved through the application of the BIM Maturity Matrix, represented by the acronym BIM³, which measured the degree of BIM maturity of each company analyzed. Data was also collected about the operation process of the study objects in question through the application of a questionnaire to investigate the workflow in the construction process. Subsequently, the analysis of this data was constructed, based on the concepts of the BIM Maturity Matrix, identifying possibilities for rework, unforeseen expenses, purchases of excess materials, for example, according to the specifications in each phase of the project. In this sense, of the 3 offices analyzed, Company B obtained the best results regarding the skills investigated, which identified the level of maturity in relation to the use of this technological tool.
Keywords: Modelagem da Informação da Construção (BIM); Building Information Modeling (BIM); Construção civil - Tecnologia; Gestão de projetos de engenharia; CNPQ::ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL::PROCESSOS CONSTRUTIVOS